2023
DOI: 10.1007/s11356-023-25948-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal change and driving factors of ecological status in Inner Mongolia based on the modified remote sensing ecological index

Abstract: Remote sensing monitoring of regional ecological quality has advanced significantly with the rapid developments of remote sensing technology. At present, remote sensing ecological index (RSEI) has been widely used in ecological status monitoring. However, RSEI was proposed for urban environments, and the rationality and accuracy of its applicability to desert-dominated arid zone ecosystems need to be demonstrated. Therefore, in this study, we incorporated desertification monitoring index (DMI) and salinity mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The saline-alkali land area in China is about 99.13 million hectares, accounting for about 5% of the available land area [32,33], the utilization of which will greatly improve the supply of agricultural products. For example, about 23% of the land in Inner Mongolia is saline land, covering a comprehensive area of up to 7.63 million hectares [34]. In recent years, many scientists have conducted a significant amount of research on the negative effects of salt stress on soybeans.…”
Section: Application Analysis Of Rhizobia From Different Areasmentioning
confidence: 99%
“…The saline-alkali land area in China is about 99.13 million hectares, accounting for about 5% of the available land area [32,33], the utilization of which will greatly improve the supply of agricultural products. For example, about 23% of the land in Inner Mongolia is saline land, covering a comprehensive area of up to 7.63 million hectares [34]. In recent years, many scientists have conducted a significant amount of research on the negative effects of salt stress on soybeans.…”
Section: Application Analysis Of Rhizobia From Different Areasmentioning
confidence: 99%
“…Thus, the MRSEI can represent the environmental quality using these five indicators. To evaluate the effectiveness of the MRSEI, this paper compared the RSEI and MR-SEI [24,37,38], as shown in Figure 3. The RSEI and MRSEI roughly had the same trend in the evaluation of the environmental quality in Lanzhou City, but there were differences in the spatial distribution and degree.…”
Section: Validity Of the Mrsei Modelmentioning
confidence: 99%
“…Wang et al [14] constructed a drought remotesensing index for EEQ monitoring in the Central Asia Aral Sea Basin by incorporating landdegradation indicators. Bai et al [15] developed an enhanced ecological index for remotesensing applications in arid areas by integrating desertification and salinity indicators. These studies have shown that the improved index is more applicable to arid regions.…”
Section: Introductionmentioning
confidence: 99%